The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/ajg.2016.434
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing the Low FODMAP Diet vs. Modified NICE Guidelines in US Adults with IBS-D

Abstract: In this US trial, 40-50% of patients reported adequate relief of their IBS-D symptoms with the low FODMAP diet or a diet based on modified NICE guidelines. The low FODMAP diet led to significantly greater improvement in individual IBS symptoms, particularly pain and bloating, compared with the mNICE diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
334
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(362 citation statements)
references
References 28 publications
16
334
2
10
Order By: Relevance
“…One study randomised 38 patients to low FODMAP advice and 37 to standard dietary advice for 4 weeks with a clinical response (≥50 point reduction in IBS-SSS) reported in 50% in the low FODMAP group and 46% in the standard advice group, with no difference between groups 75. In the second RCT, although there was no difference in proportion of patients achieving the adequate relief endpoint, there were a greater number of pain responders in the low FODMAP group (51%) compared with standard advice (23%, p=0.008), as well as a greater magnitude of response of multiple individual symptoms (abdominal pain, bloating, stool consistency frequency and urgency) 70. These data on individual symptom response are consistent with previous findings of a non-randomised comparative trial that reported a significant difference in the numbers responding to low FODMAP dietary advice (76%) compared with standard National institute for Health and Care Excellence (NICE) guideline dietary advice (54%) 63.…”
Section: The Low Fodmap Dietmentioning
confidence: 89%
“…One study randomised 38 patients to low FODMAP advice and 37 to standard dietary advice for 4 weeks with a clinical response (≥50 point reduction in IBS-SSS) reported in 50% in the low FODMAP group and 46% in the standard advice group, with no difference between groups 75. In the second RCT, although there was no difference in proportion of patients achieving the adequate relief endpoint, there were a greater number of pain responders in the low FODMAP group (51%) compared with standard advice (23%, p=0.008), as well as a greater magnitude of response of multiple individual symptoms (abdominal pain, bloating, stool consistency frequency and urgency) 70. These data on individual symptom response are consistent with previous findings of a non-randomised comparative trial that reported a significant difference in the numbers responding to low FODMAP dietary advice (76%) compared with standard National institute for Health and Care Excellence (NICE) guideline dietary advice (54%) 63.…”
Section: The Low Fodmap Dietmentioning
confidence: 89%
“…However, a more recent randomised, controlled trial has shown that a diet low in FODMAPs reduces symptoms of IBS as well as traditional dietary advice,30 and there was no significant difference in the primary end point of the proportion of patients reporting adequate relief of IBS-D symptoms by ≥50% during intervention weeks 3 and 4 of the 4-week trial 31. In the latter study, a secondary end point was a 30% reduction in mean daily abdominal pain score during 2 of the 4 weeks in the study, and this pain end point was significantly reduced by low FODMAP diet compared with control diet.…”
Section: Current Approaches To Manage Visceral Pain In Patients With Ibsmentioning
confidence: 96%
“…Table 1 reports the clinical trials that are available in the literature on the effect of a low-FODMAP diet in IBS patients [3,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. In general, most studies and one meta-analysis [6] have shown that IBS symptoms, particularly bloating and abdominal pain, may benefit from this treatment.…”
Section: Efficacy Of the Low-fodmap Diet: What Is The Quality Of Tmentioning
confidence: 99%
“…Indeed, studies comparing the efficacy of the low-FODMAP diet vs. proper dietary advice for IBS did not show a clear-cut advantage of the low-FODMAP diet: (a) in a US trial, 40%–50% of patients reported adequate relief of their IBS with diarrhea symptoms with the low-FODMAP diet or a diet based on modified NICE guidelines, even though the low-FODMAP diet led to significantly greater improvement in individual IBS symptoms, particularly pain and bloating, compared with the NICE diet [31]; (b) in a Swedish study the severity of IBS symptoms was reduced in both the low-FODMAP and the conventional IBS diet groups, at the end of a four-week period of treatment [26]. …”
Section: Efficacy Of the Low-fodmap Diet: What Is The Quality Of Tmentioning
confidence: 99%